Confirmation of Computational Biology Predictions on Cross-Reactivity in the Identification of American Manatee (Trichechus manatus) IgA (2024)
Immunological research in wildlife presents a unique opportunity to acquire crucial information about animal and ecosystem health. However, it is often limited by the lack of species-specific reagents and understanding of immune systems in wildlife. For the American manatee (Trichechus manatus), there is a notable gap in information regarding their immune molecules, and their impact on animal health, particularly the lack of IgA transfer in orphaned manatee calves fed with milk supplements. Immunoinformatic predictions suggested cross-reactivity between manatee IgA and anti-human polyclonal reagents due to the similarity of human and manatee IgA. The present study aimed to confirm this cross-reactivity with manatee IgA in milk samples. A dot blot assay verified the reagent's functionality and cross-reactivity with manatee samples. Immunoblotting identified the protein in manatee milk, followed by direct ELISA to optimize reagent dilutions. Cross-reactivity with a milk protein was observed in all three assays. Manatee proteins ranged from 39-46 kD, while human IgA used as a positive control weighed 61 kD. The 1:2000 reagent dilution showed the highest signal/noise ratio, indicating optimal concentration. Despite molecular weight differences preventing definitive confirmation of the identified protein as manatee IgA, partial validation of immunoinformatic predictions was achieved. These findings provide researchers a model for identifying effective reagents, reducing costs using non-specific reagents. Future studies with higher quality samples are needed to confirm and explore IgA's role in manatee health and improve the quality of the supplements used in rehabilitation centers.